2017
DOI: 10.18823/asiatefl.2017.14.3.1.380
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Relationship among Prior English Level, Self-efficacy, Critical Thinking, and Strategies in Reading Performance

Abstract: Considerable evidence indicates that self-efficacy, self-regulated learning, and academic performance are related. However, insufficient research has investigated the relationship between self-efficacy and different types of learning strategies (deep and surface processing strategies), as well as their influence on reading in EFL contexts. This study aims to investigate the effect of students' prior English proficiency on current English reading performance in school through the mediation of self-efficacy, cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
(122 reference statements)
0
10
0
Order By: Relevance
“…This method will be better carried out before the reading process begins. Students can hold discussions related to the initial knowledge of the topic contained in the reading text [38] and [39]. This step can grow both learners' self-efficacy and reading comprehension.…”
Section: Self-efficacymentioning
confidence: 99%
“…This method will be better carried out before the reading process begins. Students can hold discussions related to the initial knowledge of the topic contained in the reading text [38] and [39]. This step can grow both learners' self-efficacy and reading comprehension.…”
Section: Self-efficacymentioning
confidence: 99%
“…Fifty-eight of the 63 studies in this category refer to one, or several, of the seminal studies of deep learning from the 1970s and 1980s when defining deep learning-e.g., Marton and Säljö (1976a), Biggs (1987Biggs ( , 1993 or Entwistle and Ramsden (1983)-clearly highlighting a connection with the conceptual framework of Student Approaches to Learning (SAL). Five of the studies included in this category do not refer to any of these publications, but they use the terms deep learning (Liem, Ginns, Martin, Stone, & Herrett, 2012; van Aalst, Hing, May, & Yan, 2007), deep-level learning strategies (Matos et al, 2017), deep processing strategies (Chou, 2017) and deep cognitive learning strategies (Şen, 2016). However, the main elements in the definitions in these five publications are clearly similar to the definitions of the 58 other publications in this category.…”
Section: Deep Learning As Meaningful Learningmentioning
confidence: 99%
“…Three publications in this category, Parker and colleagues (2011;2013;2017) describe deep learning as learning for adaptive transfer: …a kind of deep learning that we call adaptive, flexible or transferable. Following Bransford and Schwartz (2000) and Hatano and Inagaki (1986), we take an understanding to be deep when it is both complex and adaptable; that is, when it is differentiated (composed of diverse cases or problems) and elaborated (much can be said about each case), yet integrated (coherent, it all hangs together) and flexible (is useable in novel problems later) (Parker et al, 2017, p. 255).…”
Section: Deep Learning As Transfer Of Learningmentioning
confidence: 99%
“…The research studies in self-efficacy area has confirmed that there are two major types of self-efficacy, namely; (1) generalized self-efficacy, the belief that one could be successful on a non-specific, global task, and (2) specific self-efficacy, the belief that one can complete a task-specific behavior from a domainspecific construct (Bandura, 1997;Green, 2003;Troia, Shankland, & Wolbers, 2012). In academic setting, especially English language teaching, there are domains in which self-efficacy is operationalized specifically, such as reading (Chou, 2017;Solheim, 2011;Taboada Barber et al, 2015;Walker, 2003), listening (Smith, Kathleen Pichora-Fuller, Watts, & La More, 2011), speaking (Bolívar-Cruz, Verano-Tacoronte, & Galván-Sánchez, 2018, and writing (Balci, 2013;Callinan et al, 2018;Ekholm et al, 2015;Huerta et al, 2017;Lichtinger, 2018;Matoti & Shumba, 2012;Prat-Sala & Redford, 2012;Villalón et al, 2015). Among those domains of self-efficacy in ELT, writing self-efficacy is an interesting and developing area for both self-efficacy and writing researches.…”
Section: Self-efficacy In Writingmentioning
confidence: 99%